Asymmetric dimethylarginine (ADMA), 4-OH-nonenal and Vitamin E levels in chronic schizophrenic patients. (30th June 2016) - Telo, Selda; Gurok, Mehmet Gurkan
Highlights: No study has examined the ADMA and HNE levels in patients with schizophrenia. Significantly higher ADMA, HNE and decreased vitamin E levels were found in chronic shizophrenic patients. ADMA and the oxidative stress may have a role in the etiopathogenesis of schizophrenia.